Minimally Invasive Surgery for the Treatment of Traumatic Monosegmental Thoracolumbar Burst Fractures: Clinical and Radiologic Outcomes of 144 Patients With a 6-year Follow-Up Comparing Two Groups With or Without Intermediate Screw. Issue 4 (May 2019) - Trungu, Sokol; Forcato, Stefano; Bruzzaniti, Placido; Fraschetti, Flavia; Miscusi, Massimo; Cimatti, Marco; Raco, Antonino
Abstract : Study Design: This was a retrospective study of the clinical and radiologic outcomes of traumatic thoracolumbar (TL) burst fractures. Objectives: We aimed to evaluate the clinical and radiologic outcomes after 6 years of follow-up of 144 patients with monosegmental TL burst fractures treated with percutaneous short-segment pedicle screw fixation, comparing two groups with versus without placement of an intermediate screw at the fractured vertebra. Summary of Background Data: Traumatic TL fractures are the most common vertebral fractures, especially at the TL junction (T10–L2). Minimally invasive surgery (MIS) is a valuable treatment option for traumatic TL burst fractures. Materials and Methods: The clinical outcomes and radiologic parameters (Cobb angle, midsagittal index, and sagittal index) of 144 patients with traumatic monosegmental TL fractures treated with MIS were evaluated preoperatively, postoperatively, and after 3 and 6 years of follow-up. Patients were categorized into a nonintermediate screw group (nISG) and an intermediate screw group (ISG), and the groups were compared. Results: There were 71 patients (49.3%) in the nISG and 73 patients (50.7%) in the ISG. The radiologic parameters improved significantly more from the preoperative evaluation to the 6-year follow-up in the ISG than in the nISG ( P <0.025). There were no significant differences in the mean Oswestry Disability Index (ODI) and Visual Analog Scale scores at the 6-year follow-up between the ISG and the nISG: 15.6% (ISG) versus 16.8% (nISG) for ODI ( P <0.1) and 2.2 (ISG) versus 2.4 (nISG) for Visual Analog Scale score ( P <0.85) ( P <0.73). Conclusions: MIS showed good clinical outcomes 6 years after surgery in both the ISG and the nISG. The additional intermediate screw significantly improved radiologic parameters but not clinical outcomes.